Windows Azure - Safari eBooks ([Redmond, Wash.?] Microsoft Corp., 2011)
"The Windows Azure Training Course was designed to help you quickly learn how to use Windows Azure, SQL Azure and the Windows Azure AppFabric. This course will also cover Windows Azure security."--Resource description page.
Title from title screen
Keywords: Windows Azure; Cloud computing; Web services; Application software -- Design; Electronic books